The effectiveness of the TAPPS strategy in the achievement of fourth-grade science biology and their reciprocal thinking - Abdlrazaq Al-bayati, Abdlrahman Ahmed (Journal of Tikrit University for Humanities, 2025)
The research aimed to identify the effectiveness of the TAPPS strategy in the achievement of fourth-grade science biology and their reciprocal thinking. The experimental method was followed, and the research was applied to a group of (62) students who were equally divided into two groups: the experimental group studied the TAPPS strategy, and the control group studied in the traditional way. The two groups were equal in some extraneous variables. Two tests were prepared: the first was an achievement test consisting of 50 multiple-choice items, and the second was a reciprocal thinking test consisting of 30 multiple-choice items with three alternatives. The tests were validated, reliable, and psychometrically sound. Statistical programs were used, and the results showed the superiority of the experimental group over the control group in the achievement and reciprocal thinking tests. The research presented some recommendations, including: encouraging fourth-grade science biology teachers to teach with the TAPPS strategy due to its positive role in developing achievement and reciprocal thinking among students.